The volatility of institutional arrangements that influence development: The case of Bram Fischer International Airport in South Africa - Masilonyane Mokhele (The Journal for Transdisciplinary Research in Southern Africa, 2018)
Hailed as the best integration of the airport and urban development, models of airport-led development are used worldwide to promote the ideal land-use mix and spatial form of airport environs. Despite the growing popularity of airport-led development, there is a lack of literature investigating how the institutional arrangements of African cities can facilitate or inhibit the implementation of such development. Using Bram Fischer International Airport in South Africa as a case study, this article describes the nature and evolution of the institutional arrangements that influence development on and around airports. Informed by the conceptual framework of historical institutionalism, the findings unveiled two contradictory phases in the evolution of institutional arrangements at the case studied: firstly, a period of harmony where all actors worked towards a common goal and, secondly, a period characterised by the absence of cooperation among stakeholders.